Recreational demand for the Swedish Mountains: A case from Storulvån and Helags during winter : An Environmental Valuation using the Travel Cost model - Tomasdotter, Amanda (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2017)
This study was conducted during the winter months in the mountains. The main objective was to estimate visitors’ values for two recreational mountain areas in Sweden, Storulvån and Helags, using the travel cost method. From the estimated values, a recreational demand and a consumer surplus has been estimated. In these mountain areas, a visitor in winter can meet different types of animals such as the beautiful bird rock ptarmigan. However, results from asking people to value the importance of different attributes indicate that it is not wildlife, but the mountain scenery and the snow, that people find most important. The travel cost method was chosen as the method for estimating a recreational demand. Therefore, a survey was conducted to obtain costs from travelling, time values and visiting patterns. The result from the study shows that the travel costs, including both stated costs and time value, range between 641 and 6138 SEK per visitor for Storulvåns mountain area depending on the visitor’s zone of origin. For Helags, travel costs were estimated to range from 1251 and 2151 SEK per visitor. The results derived for Storulvåns mountain area with a total of 3311 visitors per year spending at least one night, showed a total annual consumer surplus from the recreational demand of 2 762 650 SEK, and 834 SEK per visitor. The results derived for Helags mountain area with a total of 1167 visitors per year spending at least one night, showed a total annual consumer surplus from the recreational demand of 220 500 SEK, and 189 SEK per visitor. Denna studie genomfördes under vintermånaderna uppe i de svenska fjällen. Uppsatsens syfte var att undersöka besökarnas värdering av två fjällmiljöer i Sverige, mer specifikt Storulvåns fjällmiljö samt Helags fjällmiljö, genom att använda resekostnadsmetoden för värdering. Från de estimerade värdena har både efterfrågekurvan för rekreation i de olika fjällmiljöerna, samt ett konsumentöverskott kunnat estimeras. I dessa fjällmiljöer kan en besökare på vintern stöta på olika typer ...